2014
DOI: 10.1039/c4nr01283f
|View full text |Cite
|
Sign up to set email alerts
|

Structure sensitive chemical reactivity by palladium concave nanocubes and nanoflowers synthesised by a seed mediated procedure in aqueous medium

Abstract: Palladium nanocubes and their transformation to concave nanocubes and nanoflowers are realised by a seed mediated procedure in aqueous medium and at room temperature using cationic surfactants. The concave nanocubes and nanoflowers were found to be enclosed by high index facets. The under co-ordinated atoms present on the high index facets make these nanostructures chemically more active towards Suzuki coupling and Heck coupling reactions compared to the conventional nanocubes and spherical nanoparticles of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…This preliminary study is in-line to those carried out by other groups with similar samples. 32,57,58 While the capping ligands employed during a NC synthesis are key to shape-control and preventing aggregation, they can also be detrimental to the catalytic activity by blocking access of reactant molecules to the active surface atoms. Therefore, it is of the highest importance to 'clean' the NC surfaces without inducing structural changes.…”
Section: Resultsmentioning
confidence: 99%
“…This preliminary study is in-line to those carried out by other groups with similar samples. 32,57,58 While the capping ligands employed during a NC synthesis are key to shape-control and preventing aggregation, they can also be detrimental to the catalytic activity by blocking access of reactant molecules to the active surface atoms. Therefore, it is of the highest importance to 'clean' the NC surfaces without inducing structural changes.…”
Section: Resultsmentioning
confidence: 99%
“…For the catalytic properties of Pd nanocrystals with specific shapes and facets, the recent studies have been reported towards eletro‐oxidation and Suzuki coupling reactions . In the eletro‐oxidation of methanol, the existence of low‐coordinate atomic steps and kinks on the surface of Pd‐CNs were responsible for the superior activity.…”
Section: Resultsmentioning
confidence: 99%
“…To date, seed-mediated synthesis has been the most commonly used method for preparing concave noble metal nanoparticles. [29][30][31][32][33][34][35][36][37] In this method, seed particles with various seed shapes depending on the original reagents, such as spheres, cubes, cuboctahedrons, and rhombic dodecahedrons, are produced from seed solutions. Meanwhile, the growth solutions, in which seeds grow into concave nanoparticles, contain metal precursors, reducing agents, and structure-directing agents/surfactants/capping agents.…”
Section: Seed-mediated Synthesismentioning
confidence: 99%
“…Sreedhala et al successfully prepared Pd concave nanocubes from a seed solution via two reaction stages, including: 1) the preparation of seed Pd nanospheres and 2) the subsequent synthesis of seed Pd nanocubes in the presence of surfactant cetyltrimethylammonium bromide (CTAB) ( Figure 3A,B). [36] The obtained Pd nanocubes were then transformed into concave nanocubes in the presence of cetyltrimethylammonium chloride (CTAC) ( Figure 3C). Although the described method consisted of three stages, the relatively low reaction temperature (25-30 °C) and short reaction time (30-45 min) allowed its easy implementation.…”
Section: Seed-mediated Synthesismentioning
confidence: 99%